2015
DOI: 10.1038/ncomms9701
|View full text |Cite
|
Sign up to set email alerts
|

Resident c-kit+ cells in the heart are not cardiac stem cells

Abstract: Identifying a bona fide population of cardiac stem cells (CSCs) is a critical step for developing cell-based therapies for heart failure patients. Previously, cardiac c-kit+ cells were reported to be CSCs with a potential to become myocardial, endothelial and smooth muscle cells in vitro and after cardiac injury. Here we provide further insights into the nature of cardiac c-kit+ cells. By targeting the c-kit locus with multiple reporter genes in mice, we find that c-kit expression rarely co-localizes with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
229
4
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(265 citation statements)
references
References 42 publications
(68 reference statements)
20
229
4
8
Order By: Relevance
“…A study by Molkentin and coworkers (71) has shown that c-Kit ϩ cells minimally contribute to cardiomyogenesis but amply generate cardiac endothelial cells. A genetic c-Kit lineage tracing study from another laboratory has also shown that these c-Kit ϩ cells exhibit endothelial markers (72). These results suggest that the proportion of cardiomyocytes derived from c-Kit ϩ cells are limited.…”
Section: Discussionmentioning
confidence: 87%
“…A study by Molkentin and coworkers (71) has shown that c-Kit ϩ cells minimally contribute to cardiomyogenesis but amply generate cardiac endothelial cells. A genetic c-Kit lineage tracing study from another laboratory has also shown that these c-Kit ϩ cells exhibit endothelial markers (72). These results suggest that the proportion of cardiomyocytes derived from c-Kit ϩ cells are limited.…”
Section: Discussionmentioning
confidence: 87%
“…One may ask whether cardiac stem cells such as Kit + cells, Sca1 + cells, or epicardial progenitors contribute to new coronary endothelial cells after cardiac injury. As for Kit + cells, genetic-lineage-tracing studies showed that Kit-Cre labels a substantial number of endothelial cells in the normal heart and that those cells expand to generate more coronary endothelial cells after injury (40)(41)(42) (43), and lineage-tracing studies show that Sca1-derived cells are most endothelial cells in the normal heart (44). Our endothelial cell-tracing study suggests that these Sca1 + endothelial cells might expand after injury and that Sca1 + nonendothelial cells minimally contributed to coronary endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Attempting to shed light on these issues, Cai and Zhou and colleagues recently reported the generation of more sensitive knock-in alleles inserting conditional CRE and/or marker cassettes directly into the ATG start codon of the first Kit coding exon (Liu et al, 2016;Sultana et al, 2015). With these tools, in contrast to previous studies, KIT + cells were found to be abundant in fetal hearts and throughout postnatal life into adulthood.…”
Section: In Vivo Lineage Descendantsmentioning
confidence: 99%